INTERACTIVE METHODS IN LEARNING NEW KNOWLEDGE AND THEIR EFFECTIVENESS - Karimova Navbaxar Mahmudjanovna (Prospects for innovative technologies in science and education, 2025)
This study is dedicated to examining the significance and effectiveness of interactive methods in the process of acquiring new knowledge. The research analyzes the role of interactive methods in education, focusing on students’ motivation, creative and critical thinking skills, as well as the development of metacognitive and social competencies. Additionally, it explores how technological tools and innovative approaches can enhance the effectiveness of interactive methods. The findings indicate that interactive methods improve students’ knowledge acquisition, foster independent and creative thinking, and qualitatively enrich the learning process.